Corrosion inhibition mechanisms of 2-mercaptobenzothiazole on AA2024 T3 aluminium alloy - Vishant Garg; Maxime Magnan; Sandrine Zanna; Antoine Seyeux; Frédéric Wiame; Vincent Maurice; Philippe Marcus (npj Materials Degradation)
Abstract The mechanisms of 2-mercaptobenzothiazole (2-MBT) adsorption and corrosion inhibition on the aerospace AA2024 T3 aluminium alloy have been investigated using electrochemistry and advanced surface analyses. Electrochemical methods were used to measure the degree of corrosion protection in neutral chloride media, while advanced surface analysis techniques were employed to determine the interfacial interaction and inhibitor action mechanisms. It is shown that 2-MBT effectively inhibits corrosion of the alloy, reducing its susceptibility to corrosion attack and its corrosion rate. Surface analysis, including the use of ToF-SIMS 3-D chemical mapping, confirms 2-MBT adsorption on partially dealloyed intermetallic particles (IMPs) along with the presence of a thin 2-MBT layer on the top-most alloy surface. Chloride ions breakdown the native oxide film, allowing 2-MBT to adsorb on IMPs, thereby inhibiting further localized corrosion on these particles, while the 2-MBT layer on the surface protects the alloy matrix from surface oxidation.